An American heroine in the French Resistance : the diary and memoir of Virginia d'Albert-Lake - Albert-Lake, Virginia d', 1910-1997 (World War II--the global, human, and ethical dimension ;, 2006)
This fascinating book tells the remarkable story of an ordinary American woman?s heroism in the French Resistance. Virginia Roush fell in love with Philippe d?Albert-Lake during a visit to France in 1936; they married soon after. In 1943, they both joined the Resistance, where Virginia put her life in jeopardy as she sheltered downed airmen and later survived a Nazi prison camp. After the war, she stayed in France with Philippe, and was awarded the Légion d?Honneur and the Medal of Honor. She died in 1997. Judy Barrett Litoff brings together two rare documents?Virginia?s diary of wartime France.